ODPOWIEDZIALNOŚĆ PAŃSTWA CZŁONKOWSKIEGO ZA AKTY ORGANIZACJI MIĘDZYNARODOWEJ - Czapliński, Władysław (Wydział Prawa i Administracji UAM, 2006)
The international liability of international organisations is a relatively recent issue, which has arisen mainly out of the growing activity of organisations, especially in situations which involve violent acts that result in a breach of law. The issue of international liability is currently being codified by the UN International Law Commission and it can be predicted that the traditional position which excluded State liability for acts of international organisations will be difficult to uphold. The principles of international liability of government organisations are similar to those of State liability (with two premises still valid, i.e. the infringement of an international obligation and a possibility of assigning liability for such an infringement to an international organisation). Statutes of organisations relatively seldom refer to delictual responsibility of organisations, and when it comes to State liability, there is no uniform doctrine on that. It seems though, that an operational test administered to check, or control those who violate the law will be decisive here. Judicial decisions of international courts, and in particular the decisions of the ECHR in complaints regarding the responsibility of the EU and NATO member states, have tended to exclude State liability. Therefore, the pending decision of the International Court of Justice in the dispute currently before the Court brought in by Yugoslavia against NATO member states for using force against the Federal Republic of Yugoslavia, may turn out of key significance.
LIABILITY OF STATES AS MEMBERS OF INTERNATIONAL ORGANISATIONS FOR THE ACTIONS OF THOSE ORGANISATIONS